(untitled) (Research, Society and Development, 2022)
Introduction: Patients who are affected by cancer may develop oral manifestations resulting from anticancer treatment. Mucositis, xerostomia, radiation cavities and osteoradionecrosis are some of the sequelae resulting from this treatment. Objective: The present study analyzed the scientific production about oral problems found in patients undergoing chemotherapy and/or radiotherapy, proving the importance of preventive dentistry in these cases. Methodology: This is a bibliographic review, in which 11 scientific articles published in the last 10 years were carefully select and analyzed, found in PubMed, Lilacs and SciELO databases. Results and Conclusion: The selected articles proved the high rate of cancer patients who presented oral manifestations during or after anticancer treatment, highlighting the importance of the dentist in the multidisciplinary team that takes care of health of these patients, aiming the improvement of the prognosis of the disease and also, the quality of life of the individual, consequently increasing its longevity.